The world's best business ideas : amazing stories behind google, the internet, ATMs post-it, smart phones GPS, the PC and many more - Wallis, Ian. (Ahmedabad : Jaico Publishing House, 2019)
Amazing stories behind Google, the Internet, ATMs, post-it, smart phones, GPS, the PC and many more The most important business ideas of the last 50 years! The world has changed more in the last 50 years than in any previous half century in history. Entire industries have been created or transformed by new business ideas. And the way we all work is utterly different today from how it was 50 years ago. Game-changing products invented during this period include the pocket calculator, personal computer, email, payment systems and GPS. All of them dominate our working lives today. Hard as it is to believe, these did not exist 50 years ago. Who came up with these ideas, and how? This fascinating book tells the stories of the products, the people and the Companies behind these amazing business ideas. It is as entertaining as any novel, and will inspire anyone striving to bring their own new idea to market today. Discover: inspirational stories of innovation and perseverance a unique chronology of the biggest advances in business an insight into the impact of business ideas on society past and present.
Keywords: The world's best Business